2022
DOI: 10.1051/bioconf/20224706005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mineral nutrition on the biochemical composition of Venyaminovskoe apple cultivar fruits

Abstract: The results of a five-year study of the mineral fertilizers' effect on the chemical composition of Venyaminovskoe apple cultivar fruits are presented. It is shown that the use of soil and foliar application of nitrogen and potash fertilizers did not have a significant effect on the content of soluble solids, sugars, titrated acids, ascorbic acid, and phenolic compounds in fruits. It was established that the most significant factor affecting the chemical composition of fruits are the weather conditions of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Similar results were found in five-year studies [ 57 ], where the use of soil and foliar application of nitrogen and potassium fertilizers did not have a strong effect on the concentration of ascorbic acid and phenolic compounds in the apple fruits. It was found that under high N nutrition in apple trees, shoot growth was enhanced and the activity of phenylalanine ammonia lyase, a key enzyme involved in flavonoid biosynthesis, seemed to be downregulated, resulting in a generally decreased flavonoid accumulation [ 20 , 61 ].…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar results were found in five-year studies [ 57 ], where the use of soil and foliar application of nitrogen and potassium fertilizers did not have a strong effect on the concentration of ascorbic acid and phenolic compounds in the apple fruits. It was found that under high N nutrition in apple trees, shoot growth was enhanced and the activity of phenylalanine ammonia lyase, a key enzyme involved in flavonoid biosynthesis, seemed to be downregulated, resulting in a generally decreased flavonoid accumulation [ 20 , 61 ].…”
Section: Resultssupporting
confidence: 88%
“…In turn, Li et al [ 55 ] demonstrated that solar radiation influenced ascorbic acid only in the apple peel, while Bui et al [ 56 ] indicated that a higher accumulation of phenolics and ascorbate took place in the sun-exposed part of peel as compared to the shaded part. Significant differences in apple antioxidant content were obtained in five-year study and the weather conditions was indicated as the most significant factor [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations